2007
DOI: 10.1063/1.2730738
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of a 3C∕4H SiC polytype heterojunction formed on the Si face

Abstract: The authors report on the electronic properties of a rectifying Si face 3C∕4H SiC heteropolytype junction on n+ 4H SiC. Capacitance-voltage profiling of the junction at temperatures from 4–300K showed high apparent carrier concentration. A semiclassical model was used to explain the behavior. The model predicted a spontaneous polarization-induced valence band quantum well in the 3C, indicating a polarization charge of 9.7×1012cm−2 for 4H SiC, in good agreement with theory. The formation of a two-dimensional ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Basing on these theoretical predictions, the electronic properties of SiC heteropolytype junctions, in which a 3C-SiC layer was grown either on the C-or on the Si-terminated face of hexagonal SiC, were recently investigated by Chandrashekhar et al [148,149] using capacitance-voltage (C-V) and Hall measurements. Following these studies, a 2DEG was experimentally observed for the first time in 3C-SiC/6H-SiC (C-face) heterostructures [150].…”
Section: Interfaces Considering Different Sic Polytypesmentioning
confidence: 99%
“…Basing on these theoretical predictions, the electronic properties of SiC heteropolytype junctions, in which a 3C-SiC layer was grown either on the C-or on the Si-terminated face of hexagonal SiC, were recently investigated by Chandrashekhar et al [148,149] using capacitance-voltage (C-V) and Hall measurements. Following these studies, a 2DEG was experimentally observed for the first time in 3C-SiC/6H-SiC (C-face) heterostructures [150].…”
Section: Interfaces Considering Different Sic Polytypesmentioning
confidence: 99%
“…Therefore as alternative, hexagonal SiC substrates have been proposed using different growth techniques. In this case new electronic devices can be envisaged since due to abrupt changes in spontaneous polarization in the hexagonal SiC, two-dimensional electron or hole gas can be formed at the interface [5,6]. Even if stress in the 3C layer is considerably reduced using hexagonal-SiC instead of Si as substrate, other defects such as double positioning boundaries (DPB) and SF are still present in the 3C material.…”
Section: Introductionmentioning
confidence: 99%
“…The 3C polytype could still be of interest for its high electron drift velocity (calculated to be above 2x10 7 cm/s) [1] and electron mobility (about 1000 cm 2 /Vs) [2], a fact which will have some advantages for MOSFET devices. Higher quality 3C layers can be grown on the most common SiC hexagonal-polytype substrates, which has been demonstrated by vapor-liquid-solid (VLS) [3], sublimation epitaxy [4] and chemical-vapordeposition (CVD) [5][6][7][8]. However, double-position-boundaries (DPB) which is a twinning of the grown layer, is still a problem in thin 3C epilayers grown on hexagonal substrates.…”
Section: Introductionmentioning
confidence: 99%